2023
DOI: 10.1002/adma.202305195
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Insulating and Moisture‐Resilient Foams Based on Upcycled Aramid Nanofibers and Nanocellulose

Andi Di,
Carina Schiele,
Seyed Ehsan Hadi
et al.

Abstract: Low‐density foams and aerogels based on upcycled and bio‐based nanofibers and additives are promising alternatives to fossil‐based thermal insulation materials. We have prepared super‐insulating foams from upcycled acid‐treated aramid nanofibers (upANFA) obtained from Kevlar® yarn and tempo‐oxidized cellulose nanofibers (CNF) from wood. The ice‐templated hybrid upANFA/CNF‐based foams with an upANFA content of up to 40 wt.% displayed high thermal stability and a very low thermal conductivity of 18–23 mW m−1 K−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The thermal conductivity in the radial direction (Figure 4a) is 4 to 7 times lower than the thermal conductivity in the axial direction (Figure 4b), which is consistent with previous studies on anisotropic nanocellulose-based hybrid foams. [59,60] The thermal conductivity in the axial direction (Figure 4b) increased with increasing relative humidity (RH) while the thermal conductivity in the radial direction (Figure 4a) displayed a U-shaped RH-dependence. Previous studies on hygroscopic CNC and CNF-based anisotropic foams [53,61] found a similar RH-dependence of the radial thermal conductivity, which was related to a competition between a humidity-induced swelling that increased phonon scattering at low and intermediate RH, and a replacement of air with water at higher relative humidity.…”
Section: Anisotropic Heat Transportmentioning
confidence: 99%
“…The thermal conductivity in the radial direction (Figure 4a) is 4 to 7 times lower than the thermal conductivity in the axial direction (Figure 4b), which is consistent with previous studies on anisotropic nanocellulose-based hybrid foams. [59,60] The thermal conductivity in the axial direction (Figure 4b) increased with increasing relative humidity (RH) while the thermal conductivity in the radial direction (Figure 4a) displayed a U-shaped RH-dependence. Previous studies on hygroscopic CNC and CNF-based anisotropic foams [53,61] found a similar RH-dependence of the radial thermal conductivity, which was related to a competition between a humidity-induced swelling that increased phonon scattering at low and intermediate RH, and a replacement of air with water at higher relative humidity.…”
Section: Anisotropic Heat Transportmentioning
confidence: 99%